Gardez le lien avec la communauté - The English Speaking Catholic Council (ESCC) (2004)

Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)